Messing with the enemy : surviving in a social media world of hackers, terrorists, Russians, and fake news - Watts, Clint (Harper, an imprint of HarperCollinsPublishers, 2018)
Former FBI Special Agent and leading cyber-security expert offers a devastating and essential look at the misinformation campaigns, fake news, and electronic espionage operations that have become the cutting edge of modern warfare - and how we can protect ourselves and our country against them. Shocking, funny, and eye-opening, this is a deeply urgent guide for living safe and smart in a super-connected world.